Current Clinical and Pharmacological Approaches to the Prescription of Loop Diuretics in Patients with Chronic Heart Failure - N. M. Gafurova; E. V. Shikh; O. D. Ostroumova (Рациональная фармакотерапия в кардиологии, 2020)
Heart failure (HF) is a growing public health problem with an estimated prevalence of 38 million patients worldwide. Congestion and formation of edema – are typical symptoms of heart failure. Diuretics are the mainstay of therapy in heart failure and are used to relieve congestion and improve exercise tolerance. Also, the administration of diuretics should be considered to reduce the risk of HF hospitalization. Loop diuretics are used by nearly 80% of all chronic HF patients and remain the drugs of choice. Although diuretics are one of the most prescribed classes of drugs, recommendations for their titration scheme for long-term use have not yet been finalized, nor have there been major prospective randomized controlled studies on the effect of diuretics on morbidity and mortality. A Cochrane meta-analysis has shown that in patients with chronic HF, loop and thiazide diuretics might reduce the risk of death and worsening of HF in comparison to placebo and could lead to improved exercise capacity. Guideline recommends the use lowest possible dose of diuretics due to probable electrolyte disturbances, further neurohormonal activation, accelerated kidney function decline, and symptomatic hypotension. Diuretic resistance is associated with an unfavorable prognosis and an increased risk of readmission. There are significant pharmacokinetic differences between the loop diuretics. Compared with furosemide, torasemide has a high bioavailability irrespective of food intake, and carries a longer half‐life and duration of effect; also, the benefits of torasemide are its additional anti-fibrotic and neurohormonal effects. Optimization of diuretic therapy in patients with HF remains a challenge and requires further research, as well as an individual approach to patients, since there is no convincing evidence base.